Al-Fi’il al-Ṡulāṡī al-Muta’addī Fī Film Kartūn “al-Qiṭ al-Ḍāi’” - Laely Yuliani Said; Limpo, Marwah; Fitriani; Abidin, Zaenal (Universitas Islam Negeri Alauddin, 2024)
Abstract This study discusses about fi'il ṡulāṡī muta'addī (transitive verb) used in the cartoon film